An Electrochemical-Based Point-of-Care Testing Methodology for Uric Acid Measurement - Yuetong Zhao; Xia Song (Journal of Analytical Methods in Chemistry)
Point-of-care technology (POCT) is an important method in clinical testing in the future, which can achieve the purpose of rapid analysis. In this work, we assembled an electrochemical POC sensor for uric acid (UA) by surface modification of a screen-printed electrode. Copper nanowires were used as electrode modifiers to achieve high-performance electrochemical oxidation of UA. This electrochemical sensor can achieve linear detection of UA in the range of 10 μM to 2 mM. The detection limit of the sensor was calculated to be 2 μM. Although the detection performance of this sensor is not competitive with high-performance electrochemical sensors, it has been able to meet the needs of POC detection. At the same time, the sensor has excellent anti-interference performance. It has also been used successfully to test urine and serum samples from healthy and gout patients.